Opening the Window on Comprehensible Pronunciation After 19 Years: A Workplace Training Study. Issue 3 (21st July 2014) - Derwing, Tracey M.; Munro, Murray J.; Foote, Jennifer A.; Waugh, Erin; Fleming, Jason
<x xml:space="preserve">Abstract</x> We present the outcomes of a pronunciation training program conducted in a workplace setting with second language speakers who had lived in an English‐speaking environment for an average of 19 years. The research questions concerned whether improvement would occur in the learners' perception of certain segments and prosody; in the comprehensibility, accentedness, and fluency of their productions as judged by listeners; and in their speech intelligibility. Despite seemingly stable speech patterns, pre‐ and postintervention tests demonstrated significant improvement in perception and in comprehensibility and intelligibility. However, no difference was noted in fluency, and accent was perceived to be stronger in one posttest. Thus the pronunciation instruction was effective, even in putatively fossilized individuals. This study contributes to research showing the partial independence of accent and other speech dimensions.